2019
DOI: 10.1098/rsos.181972
|View full text |Cite
|
Sign up to set email alerts
|

High-energy diet enhances spermatogenic function and increases sperm midpiece length in fallow deer ( Dama dama ) yearlings

Abstract: Nutrition is a major factor involved in the sexual development of livestock ruminants. In the male, a high-energy diet enhances the reproductive function, but its effects on the underlying processes such as spermatogenic efficiency are not yet defined. Moreover, the possible changes in sperm size due to a supplemented diet remain poorly investigated. The main goal of this study was to evaluate whether a high-energy diet affects the spermatogenic activity, epididymal sperm parameters (concentration, morphology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
1
17
1
Order By: Relevance
“…Nevertheless, other factors could influence the number of oocytes recovered per ovary such as different genetic background and availability of nutritional resources. In this sense, previous studies have found the nutrition affects the reproductive physiology in fallow deer (Enright, Spicer, Kelly, Culleton, & Prendiville, 2001; Ros‐Santaella, Kotrba, & Pintus, 2019). Unexpectedly, we found the number of oocytes per doe recovered during the breeding season was lower compared to the value observed during the breeding season (Zomborszky et al., 2004).…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, other factors could influence the number of oocytes recovered per ovary such as different genetic background and availability of nutritional resources. In this sense, previous studies have found the nutrition affects the reproductive physiology in fallow deer (Enright, Spicer, Kelly, Culleton, & Prendiville, 2001; Ros‐Santaella, Kotrba, & Pintus, 2019). Unexpectedly, we found the number of oocytes per doe recovered during the breeding season was lower compared to the value observed during the breeding season (Zomborszky et al., 2004).…”
Section: Discussionmentioning
confidence: 84%
“…Although earlier studies assumed that sperm were particularly cheap to produce (see Dewsbury, 2005), the influence of resource availability on sperm production has been demonstrated in a wide spectrum of organisms. For instance, in fallow deer ( Dama dama ), a species in which females mate with several males during a given reproductive attempt (Briefer et al ., 2013), yearling males with a diet supplemented with protein and amino acids have larger testes, exhibit Sertoli cells – which play a key nutritional function during spermatogenesis – with higher workload capacities, higher concentrations of sperm within the epididymis and sperm with a longer midpiece than do non‐supplemented yearling males (Ros‐Santaella et al ., 2019). This positive effect of an enriched diet on sperm quantity and/or quality has also been repeatedly found in agronomy research (e.g.…”
Section: Ageing Costs Of Sperm Competitionmentioning
confidence: 99%
“…Finally, experimental manipulations of the quantity of resources available in the environment would also provide relevant insights. As emphasised above, the allocation to ejaculate production increases with resource availability (Zhao et al ., 2017; Ros‐Santaella et al ., 2019). Therefore, for a given level of sperm competition perceived in the environment, we can predict that males should increase their allocation to post‐copulatory competition, at no or very limited costs in terms of ageing.…”
Section: Roadmap For Future Researchmentioning
confidence: 99%
“…Similarly, on the one hand, we also found that round spermatids were the most abundant spermatogenic cells, while secondary spermatocytes were the most scarce in a tomcat’s testicular cytology [ 23 , 25 ]. This pattern is consistent across several species such as red deer ( Cervus elaphus ) [ 24 ], fallow deer ( Dama dama ) [ 26 ], alpaca ( Vicugna pacos ) [ 27 ], and gemsbok ( Oryx gazella ) [ 28 ]. On the other hand, in jaguars ( Panthera onca ), elongated spermatids are the most abundant spermatogenic cells [ 29 ].…”
Section: Discussionmentioning
confidence: 70%
“…At least 200 spermatogenic and Sertoli cells were counted per smear and classified according to the morphological criteria previously described in tomcat’s testicular cytology [ 23 , 25 ] ( Figure 2 ). The following spermatogenic indices were calculated, as previously described by Ros-Santaella et al [ 26 ]: Sertoli cell index (SEI), which is the percentage of Sertoli cells per total germ cells; spermatozoa–Sertoli index (SSEI), which is the ratio of sperm cells to Sertoli cells; meiotic index (MI), which is the ratio of round spermatids to primary spermatocytes and estimates the meiotic germ cell loss; ratio of elongated spermatids to round spermatids (ES/RS), which estimates the post-meiotic germ cell loss; ratio of elongated spermatids to total germ cells (ES/GC), which estimates the overall germ cell loss; ratio of round spermatids to Sertoli cells (RS/SC) and the ratio of elongated spermatids to Sertoli cells (ES/SC), which both estimate the Sertoli cell functionality; and the ratio of total germ cells to Sertoli cells (GC/SC), which estimates the workload capacity of Sertoli cells.…”
Section: Methodsmentioning
confidence: 99%